Ethno-medicinal Usage Ethno-medicinal Usage of Invasive Plants in Traditional Health Care Practices: A Review - Prabin Adhikari; Swastika Acharya; Sabina Sigdel; Ganga Kandel (Hasanuddin University, 2022)
Nepal is a small South Asian country with a varied geographical and bioclimatic landscape. Invasive Plant Species have already been introduced in large numbers, causing the extinction of native species and disrupting crop production, as well as degrading endangered animal habitats, changing plant species composition, and interfering with tree seedling regeneration. However, it is critical in the health treatment of rural populations in developing countries. Our study will look at and compile knowledge on the therapeutic applications of invasive plants utilized by a range of Nepalese communities. We combed through numerous websites, including Research Gate and Google Scholar, for historical and contemporary studies on the therapeutic usage of Nepal's invasive plants.24 species from 12 families of invasive alien plant species were identified to be utilized for medicinal purposes by Nepalese rural people. The 39 diseases for which medicinal plants were reported were diabetes, rheumatism, fever, ulcers, bronchitis, kidney stone, asthma, urinary insufficiency, and others. Traditional knowledge of invasive plant species' uses is diminishing due to the negative effects of invasive plant species on the ecosystem; hence, rigorous documentation of ethnomedicinal knowledge on invasive plant species is needed. Thus, the medicinal potentialities of unwanted invasive species, which are sometimes neglected by others, will provide a gem for the study world.